2003
DOI: 10.1002/ejic.200300013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oxalato‐Bridged (Oxo)vanadium(IV) Dimers Using L‐Ascorbic Acid as Oxalate Precursor: Structure and Magnetism of Two Systems

Abstract: The reaction of an aqueous solution of NH4VO3 with L‐ascorbic acid and Et4NBr has afforded [Et4N]2[(VO)2(C2O4)3‐(H2O)2]·4H2O (3). A similar reaction, in which malonic acid is also added, has furnished [Et4N]2[(VO)2(C2O4)(C3H2O4)2(H2O)2]·2H2O (4). In these syntheses the oxalate ion is derived from L‐ascorbic acid. In both the complexes the dinuclear anion is centrosymmetric. In 3 the metal atoms are displaced from the plane of the bridging oxalate anion by 0.05 Å, the corresponding displacement in 4 being 0.17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
2
16
2
Order By: Relevance
“…In aqueous studies, ascorbate radical formation near neutral and in basic solutions was reported. Prolonged storing of ascorbic acid solutions in the presence of oxygen result in formation of oxalate [91]. Oxalate formation required reaction times of at least two weeks and no oxalic acid was observed in the work presented here.…”
Section: Reaction Of Ascorbic Acid With the Dioxovanadium(v) Cation Acontrasting
confidence: 49%
“…In aqueous studies, ascorbate radical formation near neutral and in basic solutions was reported. Prolonged storing of ascorbic acid solutions in the presence of oxygen result in formation of oxalate [91]. Oxalate formation required reaction times of at least two weeks and no oxalic acid was observed in the work presented here.…”
Section: Reaction Of Ascorbic Acid With the Dioxovanadium(v) Cation Acontrasting
confidence: 49%
“…[27] 1.93 ± 0.01 -6.50 ± 0.05 0.01 ± 0.002 0.0018 ± 0.00005 3 [27] 1.95 ± 0.01 -6.25 ± 0.05 0.02 ± 0.002 -0.0004 ± 0.00005 4 [18] 1.91 -3.85 0.008 5 [16] 1 Crystallographic Studies: Intensity data were collected on a Rigaku AFC6S diffractometer with graphite-monochromated Mo-K α (λ = 0.71073 Å) radiation by using the ω-2θ scan method at room temperature. The structure was solved with direct methods and refined on F 2 with full-matrix least-squares methods using SHELXS-97 and SHELXL-97 programs, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The V 2 O 10 dimer connected by a common edge found in this compound induces a stronger antiferromagnetic coupling than the oxalato-bridged (oxo)vanadium(IV) dimer. [27] Experimental Section Materials and Analyses: All reagents were of analytical grade and were used as obtained from commercial sources without further purification. IR spectra were recorded in the 400-4000 cm - 0 g, 162 mmol), and deionized H 2 O (15 mL, 0.83 mol) with a mol ratio of about 1.0:14:29:151 was placed in a 50-mL Teflonlined stainless steel autoclave, and the autoclave was sealed, heated to 155°C under autogenous pressure for 20 d, and then cooled to room temperature at a rate of 5°C/h.…”
Section: Discussionmentioning
confidence: 99%
“…Selected bond lengths and angles for [Cu 3 (mal) 3 (phen) 3 , the most interesting feature is that there exists an additional [Cu(mal)(phen)] unit (Cu2 unit) between the Cu1 and Cu3 units. In this Cu2 unit, the Cu is coordinated by two O atoms (O6, O9) from different carboxylate groups and two N atoms (N3, N4) from a 1,10-phenanthroline ligand, forming a four-coordinate, square-planar geometry (mean Cu2-N 2.001 and Cu2-O 1.912 Å ).…”
Section: Crystal Structurementioning
confidence: 99%
“…In numerous complexes, the malonate dianion generally exhibits bidentate [1][2][3], tridentate [4][5] …”
Section: Introductionmentioning
confidence: 99%